The Stability of the Horizontal Wellbore while Drilling the Bazhenov Formation in Western Siberia; Saint Petersburg International Conference and Exhibition - Gladkov E. A. Evgeny Alekseevich; Gladkova E. E. Ekaterina Evgenjevna; Karpova E. G. Evgenija Gennadyewna; Pulkina N. E. Natalia Eduardovna (Exploration & Production in Unconventional Reservoirs, 2016)
Title screen